Effect of Co Ions on the Spectral Properties and Photostability of DNA. Issue 1 (February 2014) - Gryn, Dmytro; Yashchuk, Valeriy; Sereda, Elvira; Bulavin, Leonid; Guenet, Jean‐Michel
Summary The results of the optical absorption, fluorescence, phosphorescence in UV and visible spectral range, and effect of light irradiation on spectral properties of cobalt ions of different ratios interacted with DNA are studied. Quantity of Co ions varies from 1 metal ion per 500 base pairs of DNA to 2 ions per one base pair. Three important features were fixed: the shape of fluorescence and phosphorescence spectra of the DNA do not changes in presence of Co ions, but their intensity depends on the quantity of cobalt ions in solution; phosphorescence intensity decreases more rapidly than fluorescence intensity; the small increase of DNA photodegradation rate in presence of Co is observed.